The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jfbc.12851
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity evaluation of rosemary ethanol extract and their cellular antioxidant activity toward HeLa cells

Abstract: Rosemary ethanol extract (REE) from Rosmarinus officinalis was identified by LC‐ESI‐MS/MS and 12 compounds were found. Among them, rosmarinic acid (389.78 μg/mg in REE), luteolin‐3ʹ‐O‐glucuronide (325.58 μg/mg), luteolin‐5‐O‐glucuronide (120.92 μg/mg), and geniposide (120.83 μg/mg) are the major components. The antioxidant activity evaluation of REE by off‐line HPLC methods indicated that among the 12 compounds, rosmarinic acid had the strongest scavenging activities in both DPPH· and ·OH. The cytotoxicity exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
0
11
1
Order By: Relevance
“…The rosemary powder provided 8 mg of rosmarinic acid, the main component, daily. Although 1,8-cineole, carnosic acid, and luteolin have been reported to be in rosemary essential oils [21] and ethanol extracts [10,22], these were not detected in our rosemary hot-water extract.…”
Section: Test Foodscontrasting
confidence: 68%
See 1 more Smart Citation
“…The rosemary powder provided 8 mg of rosmarinic acid, the main component, daily. Although 1,8-cineole, carnosic acid, and luteolin have been reported to be in rosemary essential oils [21] and ethanol extracts [10,22], these were not detected in our rosemary hot-water extract.…”
Section: Test Foodscontrasting
confidence: 68%
“…Rosemary essential oils and extracts obtained by ethanol extraction include carnosic acid, luteolin, and the aroma component 1.8-cineole [10,21,22]. It is believed these ingredients also improve emotion and sleep quality [42,43]; however, these components were not detected in our rosemary hot-water extract.…”
Section: Discussionmentioning
confidence: 80%
“…The solutions of 50 mg/ml EOSA, 1 × 10 –2 mol/L DPPH, 1.0 mol/L ferrous sulfate, 15% hydrogen peroxide, and 3.85 mg/ml ABTS were prepared according to the previous works of literature (Jiang et al., 2013; Nie et al., 2019; Zhao et al., 2017). The working solutions were then obtained by appropriately diluting the relative stock solutions.…”
Section: Methodsmentioning
confidence: 99%
“…provide health benefits to consumers (Li, Gao, & Lou, 2019). A recent report also showed that glycosides were the major polyphenolic compounds in the bioactive ethanolic extract of rosemary leaves (Nie et al, 2019). Among all the compounds, chlorogenic acid and quercetin are considered as potent antioxidative, anti-inflammatory, and anti-carcinogenic agents (Silinsin & Bursal, 2018).…”
Section: Total Polyphenol Content (Tpc) Total Flavonoid Content and Identification Of Major Polyphenolic Compoundsmentioning
confidence: 99%